Analysis, design and implementation of a web site for a club of virtual chess - Guevara Cadena, Johnny David (2009)
The constant technological advance demands to us to in line improve certain activities that have been taken of a same way per years, like for example a Game of Chess. "Virtual Chess Club", has been developed with the objective anywhere in the world to allow the live connection between opposing professional and become fond of, dispersed chess players, conforming a Virtual Club, disputing started off in line, storing them in Data Base, that soon can be consulted, providing to the chess players of a powerful tool for its sport preparation. In the first part of this document the theoretical and technical analysis and foundations for the development of our Web site are specified, Virtual Chess Club. Later it is made Design and the presentation of the steps that were followed for the implementation.